Obtaining Evidence Protected by Banking Secrecy through European Investigation Order in Preparatory Proceedings. Remarks from the Polish Perspective - Smarzewski, Marek Ryszard (Review of European and Comparative Law, 2023)
The subject matter of considerations undertaken in the paper is the issue of obtaining evidence entailing banking secrecy under the European Investigation Order at the stage of the preparatory proceedings from the Polish perspective. The examination of the described evidence activity is often necessary to make key findings, for example, in the field of the data on bank accounts or bank transactions. Actions taken in this regard may concern the monitoring of banking operations and may also be used for establishing financial links between entities operating in different European Union Member States. The procedure for applying the European Investigation Order generates many problems in the analysed scope, in particular at the stage of the preparatory proceedings, starting from determining the authority competent to issue the European Investigation Order, to the need to consider legitimacy of obtaining the consent by the prosecutor to exempt from banking secrecy in order to further request for the required information. Against the background of the issues presented in the article, an attempt was made to analyse the normative institution of the European Investigation Order, used for obtaining evidence covered by banking secrecy, and to show the model that determines its optimal functioning in the face of existing problems in the application challenges related to the European cooperation in this area.